PENYELARASAN PERUBAHAN PERUNTUKAN KAWASAN HUTAN DI KAWASAN INDUSTRI â€œSuatu keniscayaan bagi perbaikan lingkungan, kenyamanan dan keindahan alamâ€ - Nitibaskara, Tb Unu; Endom, Wesman (Universitas Nusa Bangsa, 2014)
Since industrial area around Bekasi-Karawang-Purwakarta enhanced, it is necessary considering the review of alternate optimally function of the forest production as conservation area. It is important due to existence of District autonomy which can arrange the plan and manages natural resources and not only for environment, but also from economic and social aspects. The reasons are (1) benefit in enjoying transportation view; clean air along journey with green plantations, (2) indirectly as media education and counselling for how important of existence forest, (3) production of wood yield cannot real supplier that could answer demand wood requirement, (4) wood product unfavourable quality, (5) of [his/its] function for environmental health as absorber of dirty air as effect of air pollution from industrial and the reduce noise, ( 6) function of natural beauty with variation of other lifeâ€™s and birds. Others benefit among others are (1) laboratory of various target of biological research and conservation, ( 2) medium of development for recreation service , ( 3) sample for environmental greening movement in more proactive and ( 4) civilizing movement for all birds flown freely.